Book Review: The Tawhidi Methodological Worldview; A Transdisciplinary Study of Islamic Economics - Rusydiana, Aam Slamet (SMART Insight, 2025)
This article critically reviews the grand idea of the Tawhidi Methodological Worldview (TMW) developed by Masudul Alam Choudhury as a new epistemological and methodological framework in Islamic economics. Departing from the law of Tawhid (the oneness of Allah) as its ontological foundation, TMW rejects the dichotomy between rational-material science and moral-spiritual values that dominates the Western paradigm. Through the Tawhidi String Relation (TSR) model, Choudhury formulates a theory of the unity of knowledge that transcends disciplinary boundaries, unifying science, morality, and social reality into an organically interconnected system. This article seeks to explain the basic concepts, epistemological structure, and transdisciplinary implications of TMW for the reconstruction of Islamic economics. This study indicates that TMW offers a new direction for the development of an integrative, dynamic, and universal welfare (maslahah)-oriented Islamic science.